Peculiarities of the psychoemotional state and stress response of combatants with traumatic injuries of the great vessels of the extremities with different extents of surgical intervention - Koshchii Владислава (Psychosomatic Medicine and General Practice, 2019)
Aim. The aim of the work was to investigate the peculiarities of psycho-emotional state and stress response of combatants with traumatic injuries of the main vessels of the extremities with different volume of surgery, to identify personalized targets of psychological correction of psychological maladjustment for this group of patients. Materials and methods. To achieve this goal on the basis of the Military Medical Clinical Center of the Northern region, 150 combatants were examined during 2018-2019 who were there for treatment after participating in hostilities. The main group (MG) consisted of 120 people who had traumatic injuries of the main vessels of the extremities, the comparison group (CG) - 30 fighters without somatic combat injuries. According to the criterion of the volume of surgery, MG patients were divided into two subgroups - MG1 - 60 injured with traumatic injuries of the main vessels of the extremities, who managed to save the injured limb after surgery; MG2 - 60 wounded with traumatic injuries of the main vessels of the extremities, which led to amputation of the extremities. The study used clinical-psychological, psychodiagnostical and statistical methods. Results. As a result of the study we were able to confirm the previous hypothesis of greater severity and variability of signs of post-stress psychological maladjustment in the form of distortion of the psycho-emotional sphere and stress response in people with combined mental and somatic combat trauma, compared with combatants without somatic injuries. According to all the studied parameters - general psychopathological symptoms, manifestations of depressive, anxiety and stress response - the lowest severity of all indicators was observed in somatically uninjured fighters. The Global Severity Index (GSI), the index of severity of psychopathological manifestations (PSI), the total indicators of depression and pathological anxiety (at the level of moderate) were higher among fighters who lost a limb due to injury, however, in persons with preserved limbs distress (PDSI) against the background of slightly lower rates of depression and anxiety (at the level of mild depression and mild with a tendency to moderate anxiety). It is expected that for combatants who survived limb amputation due to injuries, higher levels of both post-traumatic stress response (due to double mental and somatic combat trauma) and acute stress disorder (both reactions to limb loss due to surgery) indicators, and for individual symptoms. However, injured combatants who managed to save their limbs as a result of surgery had significantly higher rates of "survivor guilt" than those who survived amputation. In combatants without combat traumatic injuries, most indicators, as well as integrated indicators of stress response were significantly lower than those of wounded with injuries to the main vessels of the extremities. Conclusions. The established patterns are important to take into account when developing measures for psychocorrection of psychological maladjustment of combatants with damage to the main vessels of the extremities.